Adjudicating Separation of Powers: Lessons From The European Court of Human Rights for A Future Asian Human Rights Mechanism? - Lee, Seokmin (Universitas Muhammadiyah Yogyakarta, 2021)
Efforts to build a regional human rights mechanism in Asia are being renewed. Separation of powers adjudication will be inevitable if the right of access to court is included in the new mechanism. This is significant since the potential for separation of powers cases involving human rights issues in Asia is high. An Asian human rights mechanism must take this possibility into account, since adjudicating on such issues may severely impact its stability and long-term viability. A mechanism based on existing regional systems such as the ECHR can seek to minimize these risks via institutional solutions. On the other hand, an Asian mechanism can side-step these issues in the short term by focusing on a narrow set of rights, which minimize the potential for raising issues of separation of powers. In the long term, however, a complete charter of fundamental rights cannot ignore separation of powers issues being linked with human rights. The aim of this paper is to highlight both the inevitability and risks of adjudicating cases involving a nexus between separation of powers and human rights by a regional human rights court.